Human Induced Pluripotent Stem Cell Models of Frontotemporal Dementia With Tau Pathology - Kühn, Rebekka; Mahajan, Aayushi; Canoll, Peter; Hargus, Gunnar (Frontiers in Cell and Developmental Biology, 2021)
Neurodegenerative dementias are the most common group of neurodegenerative diseases affecting more than 40 million people worldwide. One of these diseases is frontotemporal dementia (FTD), an early onset dementia and one of the leading causes of dementia in people under the age of 60. FTD is a heterogeneous group of neurodegenerative disorders with pathological accumulation of particular proteins in neurons and glial cells including the microtubule-associated protein tau, which is deposited in its hyperphosphorylated form in about half of all patients with FTD. As for other patients with dementia, there is currently no cure for patients with FTD and thus several lines of research focus on the characterization of underlying pathogenic mechanisms with the goal to identify therapeutic targets. In this review, we provide an overview of reported disease phenotypes in induced pluripotent stem cell (iPSC)-derived neurons and glial cells from patients with tau-associated FTD with the aim to highlight recent progress in this fast-moving field of iPSC disease modeling. We put a particular focus on genetic forms of the disease that are linked to mutations in the gene encoding tau and summarize mutation-associated changes in FTD patient cells related to tau splicing and tau phosphorylation, microtubule function and cell metabolism as well as calcium homeostasis and cellular stress. In addition, we discuss challenges and limitations but also opportunities using differentiated patient-derived iPSCs for disease modeling and biomedical research on neurodegenerative diseases including FTD.